On principal element lattices - KOÇ, SUAT; TEKİR, ÜNSAL (SPRINGER BASEL AG, 2021)
In this paper, we study principal element lattices, Prufer lattices and Q-lattices. Also, a necessary and sufficient condition is given for a principally generated C-lattice to be a finite direct product of proper Dedekind domains.
Keywords: Prü fer lattice; S-lattice; Principal element lattice; l-prime element; Principal element